A notícia e suas múltiplas contribuições para a compreensão leitora no ensino fundamental I - Costa, Josivete Santos da (2017)
The present work proposal has the concern of discussing the practice of reading the students of the 5th year of elementary school, considering the understanding and meaningful learning in the classroom of what is proposed by the Genre News. For this, it was hypothesized that the continuous use of the News in the formation of readers could minimize the difficulties of reading and understanding found among the students of Elementary School. In order to prove this hypothesis, we considered as theoretical contributions on strategies of reading authors such as Solé (1998); Marcuschi (2002), Kleiman (2013), Koch; Elias (2014) and the official PCN documents (1997, 1998, 2001). The methodology adopted in the research was action research, because it is relevant to use a pedagogical intervention proposal divided into two parts: one, of a theoretical nature to base a work practice for the Basic School; And another, of a practical nature - a proposal of intervention work using the Genre News to the students of the 5th year of Elementary School. The result that has been reached indicates that the continuous use of the News Genre in Elementary School contributes positively to minimize the difficulties found in the reading formation and the significant learning of the students.